LDPC code with Dynamically adjusted LLR under FSO turbulence channel. Issue 1 (May 2021) - Cao, Pin; Rao, Qingmei; Yang, Jian; Liu, Xingxing
Abstract: With the development and progress of space technology, more and more scholars begin to study FSO communication. The free-space optical communication takes the atmosphere as the medium, and the signals are susceptible to atmospheric turbulence. As an important channel code, LDPC code is applicable to almost all channels. In order to obtain better communication performance, we propose dynamically adjusted log-likelihood ratio (LLR) as the input of LDPC decoder in this paper. Compared with the traditional LLR input, the simulation results show that the LDPC code based on dynamically adjusted LLR has stronger anti-turbulence ability and better error performance under different atmospheric turbulence conditions. Coherent communication system with PM-QPSK modulation format under FSO turbulence channel is utilized in our work.